From Fragmentation to Financial Integration in Europe - Enoch, Charles (International Monetary Fund, 2013)
From Fragmentation to Financial Integration in Europe is a comprehensive study of the European Union financial system. It provides an overview of the issues central to securing a safer financial system for the European Union and looks at the responses to the global financial crisis, both at the macro level-the pendulum of financial integration and fragmentation-and at the micro level-the institutional reforms that are taking place to address the crisis. The emerging financial sector management infrastructure, including the proposed Single Supervisory Mechanism and other elements of a banking union for the euro area, are also discussed in detail.